For one more day - Albom, Mitch (New York : Hyperion, 2006)
Grieving over the death of his mother, Charles "Chick" Benetto uses alcohol as a crutch to deal with his loneliness, isolation, and depression and the disintegration of his life, until an encounter with his mother's ghost brings him new awareness and leads him to attempt to put his life back together.
Keywords: Mothers and sons -- Fiction; Mothers -- Death -- Fiction; Psychological fiction